Transition-Metal-Free Functionalization of Saturated and Unsaturated Amines to Bioactive Alkaloids Mediated by Sodium Chlorite - Romero-Ibañez, Julio; Fuentes, Lilia; Sartillo-Piscil, Fernando (Synlett, 2020)
New approaches to the synthesis of alkaloids through the straightforward functionalization of C(sp3)–H and C(sp2)=C(sp2) bonds of simple five- and six-membered-ring N-heterocycles are highlighted. The direct functionalization of pre-existing N-heterocycles to advanced alkaloids intermediates is a chemical operation that commonly requires the intervention of transition or precious metals. Regardless the inherent unwanted waste production, the high economical cost of many transition-metal catalysts limits their use globally. Here, we account our efforts directed toward the synthesis of bioactive alkaloids under an economic and ecological fashion by using NaClO2 as the key activating or oxidizing reagent that substitutes the use of transition-metal catalysts. While undesired metal wastes are collected during the extraction process of a transition-metal-catalyzed reaction, innocuous NaCl is the commonly product waste when NaClO2 is employed in our chemical transformations. Beginning with the synthesis of 2,3-epoxyamides from allyl amines, we concluded with the functionalization of multiple and remote C(sp3)–H and C(sp3)–C(sp3) bonds in piperidine rings that enabled the preparation of important bioactive alkaloids. For the latter functionalization, a precise amount of co-oxidant reagent (NaOCl) and radical 2,2,6,6-tetramethylpiperidinyloxy (TEMPO) were needed.1 Introduction2 Direct Chemical Method for Preparing 2,3-Epoxyamides3 Dual C(sp3)–H Oxidation of Cyclic Amines to 3‑Alkoxyamine Lactams4 Electrochemical Deamination of 3-Alkoxyamine Lactams5 Direct C–H Oxidation of Piperazines and Morpholines to 2,3-Diketopiperazines and 3-Morpholinones, Respectively6 Transition-Metal-Free Triple C–H Oxidation7 Deconstructive Lactamization of Piperidines8 Conclusion
Keywords: sodium chlorite; amines; alkaloids; C–H oxidation; transition-metal free